Removal of oil and grease from industrial wastewater by using advanced oxidation process - Mthethwa, Sikhumbuzo Abednigo (Vaal University of Technology, 2022)
The aim of this study was to removal of oil and grease from the wastewater sample from Fuel Firing Systems (FFS) refinery factory contaminated with the Fats Oil and Grease (FOG), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS) and Total Organic Carbon (TOC). The wastewater sample was investigated using hydrogen peroxide. The sample was treated at the controlled flow rate in the ozonation reactor, this was done by bubbling the ozone through a stone diffuser at the ratio of 1 litre of wastewater sample and 2 mL of hydrogen peroxide on the first run. Each experiment run for 30 min each sample were taken 15 min time intervals for treatment of wastewater sample. The second run 1 litre of wastewater sample, 3 mL of hydrogen peroxide for 45 min treated. The third run 1 litre of wastewater 4ml of hydrogen peroxide for 60 min treated and lastly fourth experiment run with 1 litre of wastewater, 5 mL of hydrogen peroxide treated. All four test run with the common flow rate of 1500 nm3/h of ozonation with the capacity of ozone generator, the first run was 40% capacity, second run was 50% through the generator. The third run was 60% and fourth run with 70% through to ozone generator. During the reaction of ozone and hydrocarbon in wastewater few drops of hydrogen peroxide were added into the solution to speed up reaction at the same time pH was controlled. The results of the experiment shown in chapter 4 the different figures in a graph form, in figure 11 Chemical Oxygen Demand (COD) treated from the Lab and the graph shown is decreasing as per time interval. In Figure 12 results of Fat Oil and Grease (FOG) after treated, the graph shown decreased as well shown less pipe clogging in the systems. In figure 13 Total Suspended Solid (TSS) after treated from the Lab, the graph shown after 30 minutes decrease in addition of Hydrogen peroxide the results from the graph increase until the end. The pH graph shown start to decrease and increase after 30 minutes pH decrease toward neutral.
M. Tech. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Fats oil; Grease; Wastewater; Fuel Firing System; Chemical Oxygen Demand; Total Suspended Solid; Total Organic Carbon; Hydrogen peroxide; Dissertations, Academic -- South Africa.; Hydrogen peroxide.; Oils and fats.; Petroleum waste.; Electrochemical analysis.